A Comparison of Cyst Formation and Management in Mobile-Bearing and Fixed-Bearing Total Ankle Arthroplasty. Issue 2 (25th April 2019) - Lachman, James; Taylor, Michel; Cody, Elizabeth; Scott, Daniel; Nunley, James A.; DeOrio, James K.; Easley, Mark E.
Category: Ankle Arthritis Introduction/Purpose: The Scandinavian Total Ankle Replacement(STAR) system and Salto Talaris(ST) total ankle system are two of the more commonly studied total ankle implants. As the STAR is one of the oldest total ankle arthroplasty (TAA) implants still in use today, most studies focus on longevity and survivorship. Reported rates of cyst formation for these two prosthesis in most series vary from 11-22% but no large study has focused on surgical management of these cysts or included patient reported outcomes after surgery. In this series, we aimed to investigate rates of cyst formation between mobile(MB) and fixed-bearing(FB) TAA and examine clinical and patient reported outcomes of bone grafting or cementing of large cysts surrounding the STAR and ST implants. Methods: A prospectively collected database at a high volume total ankle replacement center was retrospectively reviewed to identify patients who underwent TAA with either the STAR or the ST total ankle system between 2007 and 2015. Cysts were identified and measured on standard weight bearing radiographs and confirmed on computed tomography(CT) when available. Visual analog scale (VAS) score, Short Form-36 (SF-36) physical and mental component scores, Short Musculoskeletal Function Assessment(SMFA), and AOFAS hindfoot scores were collected from all patients preoperatively and then at 6 months, 1 year and annually postoperatively. Patients with a minimum 2 years follow-up who underwent revision TAA secondary to catastrophic bone cysts or who were managed with either curettage and bone grafting or curettage and cementing of bone cysts surrounding the TAA prosthesis were included in the patient reported outcomes (PRO) analysis Results: Excluding 53 patients for inadequate follow-up, 232 patients (29% female, 71% male; follow-up 6.7 years) who underwent STAR-TAA and 147 patients (26.6% female, 73.5% male; follow-up 7 years) who underwent ST-TAA were identified. Cysts <20 mm diameter occurred more often in the MB TAAs, and more often in the tibia than talus (table). Cysts >10 mm were identified in 95/232 (41%) STAR and 24/147 (16%) ST ankles. In the STAR group, 24 patients underwent cyst bone grafting (13), cementing (6) or both (8) at a mean 4.8 years. In the ST group, 14 patients underwent cyst bone grafting (6), cementing (4), or both (4) at a mean of 2.7 years. PRO data improved significantly for both the STAR and ST group in all questionnaires (p<0.05 for all). Conclusion: Mobile-bearing total ankle arthroplasty in this cohort had a higher rate of cyst formation greater than 10 mm (95/232 patients, 41%) when compared to a fixed-bearing TAA (24/147, 16.3%). Only 24/95 (25%) of STAR patients and 14/24 (58%) of ST patients required surgical intervention for cyst management. Patient reported outcomes after cyst surgery improved significantly when compared to pre-cyst management surgery and did not differ between MB and FB cohorts (p=0.424). Successful surgical management of large cyst surrounding either mobile-bearing or fixed-bearing total ankle systems can be expected based on the results of this study. Mobile-Bearing TAA Fixed-Bearing TAA Total patients (n) 232 147   Total Patients with Cysts >10mm 95(41%) 24 (16%)   Patients Requiring Cyst Surgery 24/95 (25%) 14/24 (58%) Age (years) 61.8 63.3 Sex   Male 165(71%) 107(73%)   Female 67(29%) 40(27%) Time Until Cysts Visible (years) 1.82 1.63 Cysts <20mm Diameter   Tibia 89 patients 10 patients   Talus 51 patients 4 patients   Both Tibia and Talus 29 patients 1 patients Cysts >20mm Diameter   Tibia 28 patients 4 patients   Talus 4 patients 2 patients   Both 0 Patients 2 patients Reoperation for Cyst n=24 n=14 Management mean 4.8 years post-op mean 2.7 years post-op   Bone Grafting 13 6   Cementing 6 4   Both 8 4 SF-36 Before Cyst Surgery   Physical Function 23.8 19.9   Mental Health 75.1 77.9 SF-36 After Cyst Surgery   Physical Function 68.3 67.6   Mental Health 89.4 88.8 VAS Before Cyst Surgery 62.7 59.4 VAS After Cyst Surgery 4.1 3.7